Training, incentives, and performance in below-target Indonesian retail stores: Direct effects and no detectable motivational mediation - Meydita Nur AyuNingTyas N; Pompong Budi Setiadi; Sri Rahayu (Priviet Social Sciences Journal, 2026)
Human Resource Management (HRM) theory often assumes that ability-enhancing practices, such as training, and motivation-enhancing practices, such as incentives, improve employee performance by first raising work motivation. This study tests the mediation logic in a deliberately bounded setting: 145 sales associates nested within eight below-target store units of a single Indonesian retail branch. Using reflective Partial Least Squares Structural Equation Modeling (PLS-SEM), this study estimated the direct effects of training and incentives on performance and motivation, and the specific indirect effects transmitted through motivation. Training and incentives showed positive direct effects on both motivation and self-rated performance and jointly explained 65.9% of the variance in motivation and 67.4% of the variance in performance. However, the motivation-to-performance path was positive but not statistically detectable at the 5% level (β = 0.135, p = .099), and the specific indirect effects were positive but had confidence intervals that crossed zero. Therefore, the evidence supports a cautious conclusion of no detectable mediation under these study conditions rather than proof that mediation is absent. The findings are interpreted as a boundary-condition proposition for Ability-Motivation-Opportunity (AMO)-based mediation logic, with explicit caution that motivation was operationalized as Maslowian need satisfaction rather than autonomous versus controlled motivation, performance was self-rated, and respondents were clustered within below-target stores. The practical implications for training transfer, incentive design, and performance management in similar underperforming frontline retail settings are discussed.